Adaptive Synchronization in Complex Network with Different Order Node Dynamics - Fan-di Zhang; Jin-ping Jia; Li-xin Yang (Discrete Dynamics in Nature and Society)
This paper investigates the adaptive cluster synchronization in the complex networks with different orders. By means of Lyapunov stability theory and the adaptive control technique, a novel adaptive synchronization controller is developed. To demonstrate the validity of the proposed method, the examples for the synchronization of systems with the chaotic and hyperchaotic node dynamics are presented.